Homecoming Parade Float 1965 (1965)
Homecoming float with honored personnel seated behind (including President and Mrs McPhee). Float has signs "Learn By Doing," "Upside Down Curriculum," and "Try it!" along with a train circling what appears to be an interpretation of the Poly P.